Advances in Business ICT - Mach-Król, Maria.; Mach-Król, Maria.; Pełech-Pilichowski, Tomasz.; Pełech-Pilichowski, Tomasz. (Advances in Intelligent Systems and Computing, 2014)
Futurists and scientists alike profess the coming of a new era in the history – the knowledge era. The notion of knowledge is as old as humans’ self-consciousness, but new challenges appear. The meaning of the word “knowledge” is changing from cognitive notion to a technical term denoting a structured economic resource to be actively managed. This contributed volume is a result of vivid and extremely valuable discussions held at 3rd International Workshop on Advances in Business ICT (ABICT) in Wrocław, Poland, September 9-12, 2012. The workshop focused on Advances in Business ICT approached from a multidisciplinary perspective. It provided an international forum for scientists/experts from academia and industry to discuss and exchange current results, applications, new ideas of ongoing research and experience on all aspects of Business Intelligence. ABICT has also been an opportunity to demonstrate different ideas and tools for developing and supporting organizational creativity, as well as advances in decision support systems. This book is of interest to researchers, widely understood business, public sector and IT professionals.